PSD-95-like membrane associated guanylate kinases (PSD-MAGUKs) and Synaptic Plasticity - Xu, Weifeng (2011)
Activity-dependent modification of excitatory synaptic transmission is fundamental for developmental plasticity of the neural circuits and experience-dependent plasticity. Synaptic glutamatergic receptors including AMPA receptors and NMDA receptors (AMPARs and NMDARs) are embedded in the highly organized protein network in the postsynaptic density. Overwhelming data have shown that PSD-95-like membrane associated guanylate kinases (PSD-MAGUKs), as a major family of scaffold proteins at glutamatergic synapses, regulate basal synaptic AMPAR function and trafficking. It is now clear that PSD-MAGUKs have multifaceted functions in terms of regulating synaptic transmission and plasticity. Here we discuss recent advancements in understanding the roles of PSD-95 and other family members of PSD-MAGUKs in synaptic plasticity, both as an anchoring protein for synaptic AMPARs and also as a signaling scaffold for mediating the interaction of the signaling complex and NMDARs.